2015
DOI: 10.1111/febs.13184
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin mutations causing catecholaminergic polymorphic ventricular tachycardia confer opposing functional and biophysical molecular changes

Abstract: Calmodulin (CaM) is the central mediator of intracellular Ca2+ signalling in cardiomyocytes, where it conveys the intricate Ca 2+ transients to the proteins controlling cardiac contraction. We recently linked two separate mutations in CaM (N53I and N97S) to dominantly inherited catecholaminergic polymorphic ventricular tachycardia (CPVT), an arrhythmic disorder in which exercise or acute emotion can lead to syncope and sudden cardiac death. Given the ubiquitous presence of CaM in all eukaryote cells, it is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 46 publications
7
58
1
Order By: Relevance
“…9,12,18,38 Using CD spectroscopy, in our study and others, there are no gross changes observed in tertiary structure, either in the absence or presence of Ca 2+ . 12,38 Decrease in thermal stability compared to WT is, however, a feature of most of the studied CaM mutations. 9,38 None of the CaM mutations in our, or any other, study affected Ca 2+ binding to the N-lobe.…”
Section: Accepted Manuscriptsupporting
confidence: 54%
See 2 more Smart Citations
“…9,12,18,38 Using CD spectroscopy, in our study and others, there are no gross changes observed in tertiary structure, either in the absence or presence of Ca 2+ . 12,38 Decrease in thermal stability compared to WT is, however, a feature of most of the studied CaM mutations. 9,38 None of the CaM mutations in our, or any other, study affected Ca 2+ binding to the N-lobe.…”
Section: Accepted Manuscriptsupporting
confidence: 54%
“…12,38 Decrease in thermal stability compared to WT is, however, a feature of most of the studied CaM mutations. 9,38 None of the CaM mutations in our, or any other, study affected Ca 2+ binding to the N-lobe. However, nearly all the CaM mutations resulted in decreased Ca 2+ binding in the C-lobe to varying degrees 8,9,10,17,18,38 with the exception of N54I 8,17,38 which, perhaps unsurprisingly, is located in the loop between EF-hands 1 and 2 of the N-lobe ( Figure 5).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…[111] Exome analyses of humans have identified calmodulinopathies that are also specific to one domain of CaM. [112115] Some of the identified positions, such as D95 in site III, have been found to be deleterious in both Paramecium and human studies, suggesting that their mechanisms of action are conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Videos were recorded for 20 (or 4) s at a frame rate of 100 per second. To determine heart rates, an algorithm was written in MATLAB (MathWorks, Natick, MA), as described previously (31). The supplemental videos were acquired using a Zeiss Axio Observer.Z1 microscope equipped with an AxioCam HRm camera (frame rate of five per second).…”
Section: Heart Rate Recordingmentioning
confidence: 99%